6 The experience of family carers for people with a moderate to advanced dementia within a domestic home setting: a systematic review. (30th January 2023) - James, Charles; Walshe, Catherine; Swarbrick, Caroline
Abstract : Introduction: Caring for someone with moderate to advanced dementia can be burdensome and time consuming. Understanding the nature and impact of such family caregiving at home is important to plan effective care, especially towards the end of life. Synthesising existing research will allow greater insight into this experience. Aims: To understand the experiences of family carers of people living with moderate to advanced dementia in a domestic home setting. Methods: Systematically constructed review of qualitative research using a narrative synthesis approach. Databases (MEDLINE, CINAHL, EMBASE, PsychINFO, Web of Science and Academic Search Complete) were systematically searched from 1984 onwards, combining concepts of family carers, moderate and advanced dementia, and care within a domestic home setting. Similarities and differences between papers were grouped using textual narrative synthesis. Results: Included papers (n=17) incorporated those focused on caring for people with advanced dementia (n=8), and those with moderate dementia (n=9). Family carers reported an experience of loss, burden and grief. Psychological distress was experienced due to internal conflict while caring. Although these experiences have a negative impact on general health, an improvement in the family carer's inter-relationships and the feeling of being useful were positive aspects of caregiving. Conclusions: Family carers' justifications and determinants for balancing challenges and possible distress to morals remain unclear. A complete description of all their experiences may be inadequate in conveying an acknowledgement of the illness within home-based caregiving. The caregiver-attributed personified value resulted in holding on to what remains of the care recipient for longer. Research is required to ascertain how family carers may proportionally balance their personified loss with their personified value earlier in the disease trajectory. Impact: Fear of losing a care recipient's personified value may affect how home-based caregiving is viewed by family carers and their willingness to accept or continue home-based caregiving.